Impact of sintering temperature and pH of feed solution on adsorptive removal of ammonia from wastewater using clinoptilolite based hollow fibre ceramic membrane. (February 2020) - Adam, Mohd Ridhwan; Othman, Mohd Hafiz Dzarfan; Puteh, Mohd Hafiz; Ismail, A.F.; Mustafa, Azeman; Rahman, Mukhlis A.; Jaafar, Juhana
Graphical abstract: Highlights: Fabrication of natural zeolite based ceramic membrane for ammonia removal. Effect sintering temperature of ceramic membrane was studied. 1050 °C was the best sintering temperature with compact morphological structure. The ammonia removal using the fabricated HFCM gave 96.67 % rejection at pH 7. Synergism of adsorption and separation in the HFCM enhanced the ammonia removal. Abstract: This work presented the adsorptive hollow fibre ceramic membrane (HFCM) derived from clinoptilolite for effective removal of ammonia from water. The effect of different sintering temperature of HFCM (900–1150 °C) and pH of ammonia feed solution (pH 2 – pH 11) were examined. The membranes were fully characterized by the scanning electron microscopy (SEM), mechanical strength, water permeability, X-ray diffraction (XRD), X-ray fluorescence (XRF) and zeta potential to get the better understand of its physicochemical properties and ammonia adsorption mechanism relationship. The best fabricated HFCM was produced when sintered at 1050 °C with 54.20 MPa and 228.25 L/m 2 ·h of mechanical strength and water permeability, respectively. The adsorption kinetics behavior showed that the adsorption process was best fitted to pseudo-second order kinetic model with 12.468 mg/g adsorption capacity. The morphology and negatively charged surface of the HFCM have significantly contributed to the high adsorption of the ammonia (96.67 %) from the feed solution. The maximum adsorption activities were achieved at pH 7 with 0.4 g/L HFCM within 120 min of residence time. The results indicated that the adsorptive HFCM have significant potential to be developed as simple, economical and effective remover for the ammoniacal wastewater treatment.